On Solution of Optimization Function Generated by Using Laplace Equation - Asaad Naser Hussein Mzedawee (Genius Journals, 2022)
The Laplace equation generates in each such space the equation of minimizing the residual functional. The existence and uniqueness of optimal splines are proved. For their coefficients and residuals, exact formulas are obtained. It is shown that with increasing N, the minimum of the residual functional is ( ) −5 O N , and the special sequence consisting of optimal splines is fundamental
Keywords: interpolation; spline; Chebyshev’s polynomials